POSTHUMANIST APPLIED LINGUISTICS: A TRANSPARENT ASSIGNMENT FOR WRITING RESEARCH PROPOSAL ABSTRACTS - Kweldju, Siusana; Tjandra, Christina Sandi (University of Kuningan, 2025)
Students had limited knowledge of posthumanism in applied linguistics. The assignment aimed to deepen their understanding while advancing academic and research skills. In the context of posthumanist thought, AI and chatbots are making digital technology increasingly essential in foreign language use and instruction. In posthumanist thought, machines are integral enhancements that merge with human cognition, expanding linguistic processing, multilingual interaction, and knowledge production. Pennycook’s concept of Posthumanist Applied Linguistics builds on this notion, challenging us to rethink cognition, language learning, and the interdependence of humans with nonhuman and technological entities. This study aims to discover whether doctoral students are prepared to conduct research within this emerging framework of applied linguistics. As part of the IKU 7 initiative, nineteen doctoral students enrolled in an advanced applied linguistics course were tasked with exploring this new perspective. They were guided through a transparent assignment design to develop research proposal abstracts. The design, rooted in inclusive pedagogy, ensures all students can learn by providing suitable conditions tailored to their unique needs. Quantitative analysis of the submitted abstracts revealed that students struggled to identify suitable research topics within this novel framework, due to a lack of practical knowledge in research methodology and limited understanding of posthumanist principles. Consequently, many students produced unclear titles and abstracts, with 11 out of 19 (over half) omitting the methodology section